Tapeworm parasite burden is linked to diet, body size, condition, growth, restocking and habitat use in piscivorous salmonids of a subarctic lake - Lehtonen, Topi K.; Alioravainen, Nico (Wiley-Blackwell, 2026)
Parasites affect hosts in interaction with the entire ecological community. This is particularly evident for trophically transmittedparasites, such as Dibothriocephalus tapeworms, which infect multiple intermediate fish hosts, potentially reducing their fitnessand suitability for human consumption. Here, we used a large, multi-year dataset to examine ecological underpinnings betweenDibothriocephalus burden and host traits and diet. In particular, we assessed relationships between parasite burden and bodysize, body condition, growth, restocking origin and stomach contents in the key piscivorous salmonids, Arctic charr (Salvelinusalpinus) and brown trout (Salmo trutta), in a large subarctic lake, Lake Inari. We found that Dibothriocephalus prevalence wassimilarly high in both salmonids, with decreasing parasite burden over the years. In both species, larger individuals and thosehaving three-spined (Gasterosteus aculeatus) and/or ninespine (Pungitius pungitius) stickleback remnants in their stomachs hada higher parasite burden, whereas better body condition, quicker growth, stomach contents other than sticklebacks, stocked or-igin (in Arctic charr) and river habitat (in brown trout) were associated with lower parasite counts. These findings suggest thatDibothriocephalus burden is likely to be costly, while successful foraging on non-stickleback food is associated with lower bur-den. Overall, the results highlight the intricacy of trophic accumulation of Dibothriocephalus parasites, with sticklebacks playinga special role in their transmission.
Keywords: disease; fishery; food web; ecosystems (ecology); lacustrine; parasitism; predation